2016
DOI: 10.1002/stem.2324
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells Cultured in Microfluidic Chambers Take Control of Their Fate by Producing Endogenous Signals Including LIF

Abstract: It is important to understand the role played by endogenous signals in shaping stem cell fate decisions to develop better culture systems and to improve understanding of development processes. In this study, we describe the behavior of mouse embryonic stem cells (mESCs) inside microfluidic chambers (microchambers) operated under conditions of minimal perfusion. mESCs inside microchambers formed colonies and expressed markers of pluripotency in the absence of feeders or pluripotency-inducing signals such as leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…This enhancement was shown to be the function of local volume or cell-to-volume ratio and was in part driven by the accumulation of endogenous hepato-inductive signals including HGF 12 . It is worth noting that effects of low volume cultures are not limited to hepatocytes and have been observed by us recently for stem cells as well as cancer cells 13, 14 . However, microfluidic channels used in these previous reports leave something to be desired in terms of simplicity of use, throughput and scale-up.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…This enhancement was shown to be the function of local volume or cell-to-volume ratio and was in part driven by the accumulation of endogenous hepato-inductive signals including HGF 12 . It is worth noting that effects of low volume cultures are not limited to hepatocytes and have been observed by us recently for stem cells as well as cancer cells 13, 14 . However, microfluidic channels used in these previous reports leave something to be desired in terms of simplicity of use, throughput and scale-up.…”
Section: Introductionmentioning
confidence: 68%
“…Our studies were informed and stimulated by previous reports in the field suggesting that microfluidic channels may provide a different way of culturing cells where endogenous signals may be manipulated and possibly enhanced 27-30 . Employing microfluidic chambers our lab has previously confirmed that accumulating endogenous signals were the key drivers of phenotype enhancement for a variety of cell types from undifferentiated embryonic stem cells to highly differentiated hepatocytes 12, 13 .…”
Section: Discussionmentioning
confidence: 90%
“…2a). We have previously modeled transport in a microfluidic device of a similar geometry and have determined that glucose levels were comparable to standard large volume cultures18. The oxygen tension was expected to be significantly better inside microfluidic devices because of a short distance between the cells and the gas permeable PDMS membrane comprising the roof of the device.…”
Section: Resultsmentioning
confidence: 99%
“…This is being attributed to enhanced accumulation of endogenous growth factors and autocrine signals in confined volumes of microfluidic chambers operating under diffusion dominant transport conditions (low flow regime). Such enhanced autocrine signals have been observed in stem cells182223, cancer cells24 and in primary hepatocytes1925.…”
mentioning
confidence: 87%
See 1 more Smart Citation